Effect of vitamin D supplementation on COVID-19 patients: A systematic review and meta-analysis - Zhang, Ying; Li, Jing; Yang, Min; Wang, Qin (Frontiers in Nutrition, 2023)
Objective: To systematically evaluate the impact of vitamin D supplementation on mortality, ICU admission, and the rates of mechanical ventilation or intubation among COVID-19 patients. Data sources and study selection: The PubMed, Embase, Cochrane Library, CBM, CNKI, VIP, and WanFang databases were searched from December 1, 2019 to December 31, 2022. The authors sought to identify randomized controlled trials and cohort studies that examined the relationship between vitamin D supplementation and mortality, ICU admission, and mechanical ventilation or intubation rates among COVID-19 patients. Data extraction and synthesis: Two investigators independently searched the literature, extracted the data, and assessed the quality of the included studies. The Grading of Recommendation, Assessment, Development, and Evaluation approach was used to evaluate the quality of the evidence. Meta-analysis was conducted using RevMan 5.3, STATA 15.1, and R 4.1.3 software. Results: Eight randomized controlled trials (RCTs) and eight cohort studies were included, involving 3359 COVID-19 patients. The pooled analysis of randomized controlled trials showed that vitamin D supplementation did not have a significant effect on reducing mortality (Relative Risk, RR=0.94, 95% CI 0.69-1.29, P=0.7), while the results of cohort studies indicated that vitamin D supplementation had a positive impact on reducing mortality among COVID-19 patients (RR=0.33, 95% CI 0.23-0.47, P<0.001). There was no statistically significant difference in the rates of ICU admission (RCTs: RR=0.64, 95%CI 0.38-1.08, P=0.10; cohort studies: RR=0.32, 95% CI 0.08-1.29, P=0.109) or rates of mechanical ventilation or intubation (RCTs: RR=0.77, 95% CI 0.58-1.02, P=0.07; cohort studies: RR=0.93, 95% CI 0.55-1.58, P=0.789). Conclusion: The results of this systematic review and meta-analysis suggest that vitamin D supplementation does not have a significant impact on reducing mortality, ICU admission, and the rates of mechanical ventilation or intubation among COVID-19 patients. However, due to the limited number and quality of the studies included, further high-quality studies are needed to confirm these findings.